Formulation and Evaluation Immediate Release Mucoadhesive Buccal Tablet of Midodrine HCL - Tikait , Aditi Vijay; Wankhade , Vikrant P.; Mhaske, Yukta; Atram , Sandeep C.; Bobade , Nishan N.; S. D., Pande (Asian Journal of Pharmaceutical Research and Development, 2024)
This study aimed to develop and optimize immediate-release mucoadhesive buccal tablets of Midodrine Hydrochloride, intended for rapid onset of action in treating hypotensive states. The tablets were prepared using a direct compression method, with various formulations optimized through a 32 randomized full factorial design, focusing on Crospovidone and Carbopol 934P as independent variables affecting diffusion time and mucoadhesive strength. The optimized batch F3 demonstrated superior performance, with a disintegration time of 20 seconds and an in vitro release of 98.25% within 5 minutes, meeting the criteria for immediate release. Additionally, F3 exhibited strong mucoadhesive strength, ensuring prolonged retention in the buccal cavity, and an appropriate surface pH of 6.8, compatible with the buccal environment. Stability studies conducted according to ICH guidelines confirmed that the optimized formulation maintained its integrity and efficacy under accelerated conditions. The findings suggest that the optimized F3 formulation is highly effective for buccal delivery of Midodrine Hydrochloride, offering a promising therapeutic option for patients requiring rapid antihypotensive action. The tablets exhibited efficient mucoadhesive strength, appropriate surface pH, and rapid drug release, making them promising for effective buccal drug delivery of Midodrine Hydrochloride.